KEPEMIMPINAN DALAM PENDIDIKAN ISLAM PERSPEKTIF TEOLOGIS - Siti Ruchanah (Universitas Muhammadiyah Ponorogo, 2013)
A good leadership is always associated with the success of a school. There is a significant correlation between the school performance and the effectiveness of a leader. Edmonds mentioned that a good school is led by a good leader. Still in line, Rutherford stated that an effective leader always has a clear vision, so he also has an explicit work programs. Whereas Rutter, as quoted by Sergiovanni, stated that a principal is a key of his students success and quality improvement. However, to be a good leader is not just because of a gift factor, but also needs a strong effort. A leader?s cultural and social background and the school social mission become a very influential factor towards the effectiveness of a principal leadership, it explains the social construction of school citizens and a leader?s cultural and social background then become a must to reveal the success of an education institution, such as madrasah